2020
DOI: 10.1101/2020.04.08.032250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poly (ADP-ribose) induces α-synuclein aggregation in neuronal-like cells and interacts with phosphorylated α-synuclein in post mortem PD samples

Abstract: AbstractBackgroundPoly (ADP-ribose) (PAR) is a negatively charged polymer that is biosynthesized by Poly (ADP-ribose) Polymerase-1 (PARP-1) and regulates various cellular processes. Alpha-synuclein (αSyn) is an intrinsically disordered protein (IDP) that has been directly implicated with driving the onset and progression of Parkinson’s disease (PD). The mechanisms by which αSyn elicits its neurotoxic effects remain unclear. Recent findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…α-Synuclein does not readily aggregate spontaneously (55,56) and this process is affected by the environmental conditions (57)(58)(59). The binding to lipid membranes offers a possible interface for primary nucleation events to initiate the toxic cascade of αsynuclein aggregation (47,55).…”
Section: α-Synuclein In Parkinson's Diseasementioning
confidence: 99%
“…α-Synuclein does not readily aggregate spontaneously (55,56) and this process is affected by the environmental conditions (57)(58)(59). The binding to lipid membranes offers a possible interface for primary nucleation events to initiate the toxic cascade of αsynuclein aggregation (47,55).…”
Section: α-Synuclein In Parkinson's Diseasementioning
confidence: 99%
“… 35 The molecule ABT-888, known to block the formation of PAR polymer via PARP-1/2 inhibition, has been described to potently ablate the formation of seeded inclusions in neurons and block dopaminergic neurodegeneration caused by intracranial injections of mouse preformed α-synuclein fibrils. 19 , 20 One mechanism potentially underlying these observations is that endogenous PAR polymer may critically accelerate the formation of toxic α-synuclein fibrils. 19 , 20 To generate the α-synuclein sonicated fibrils (mPFF) particles for investigation in primary neurons and in vivo injections, we monitored α-synuclein fibrillization using a real-time quaking-induced conversion assay and observed typical branched fibrillar topology of mouse α-synuclein protein assemblies generated in the presence or absence of 10 nM PAR polymer ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies provide evidence that PAR polymer and α-synuclein colocalize more in the brains of Parkinson’s disease patients than in neurologically normal controls. 19 Further, evidence in vitro and in primary neuronal cultures suggests that PAR polymer formation can both seed and accelerate α-synuclein aggregation. 19 , 20 PARP inhibition lessens the accumulation of A53T α-synuclein in transgenic models, 21 and thus might prevent α-synuclein fibril-induced inclusion formation both in primary neurons and in vivo and prevent dopaminergic neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the detailed molecular conformation and the degree of the helical twist are different from those of the polymorphs (Table S3). In addition, recent studies revealed that poly(ADP-ribose) may interact with α-synuclein in vivo 62 and induce the formation of a more toxic α-synuclein strain with distinct molecular conformations. 25 These results suggest that the interaction between co-factors and αsynuclein may direct the protein to a specific misfolding and aggregation pathway toward the distinct α-synuclein filament, highlighting the importance of cellular environments in protein misfolding and aggregation.…”
Section: Discussionmentioning
confidence: 99%